New data on the distribution of sperm whales in the Western Mediterranean highlights insufficiency of currently proposed protection measures - Brotons, Jose Maria; Cerdà, Margalida; Pirotta, Enrico; Rendell, Luke Edward (Aquatic Conservation: Marine and Freshwater Ecosystems, 2024)
As part of ongoing efforts to protect marine megafauna, especially cetaceans, in the NW Mediterranean Sea, a ‘Particularly Sensitive Sea Area’ (PSSA) was established in July 2023 by the governments of France, Italy, Spain and Monaco through the Marine Environment Protection Committee (MEPC) of the International Maritime Organisation (IMO). This is a legal instrument by which maritime traffic can be subject to advisories or controls to protect the natural environment. While the new PSSA is a significant step forward in terms of marine wildlife protection in the region, the current area only partially includes the waters that play a key ecological role for the conservation of Mediterranean sperm whales ( Physeter macrocephalus ) around the Balearics Archipelago. This isolated population is currently classified as endangered by the IUCN. Survey data from 2019 to 2022 show how the current area does not include portions of habitat in which calves are more likely to be encountered and risks displacing any maritime traffic that chooses to avoid the voluntary PSSA restrictions into habitat that is sensitive for calf survival. We argue therefore that this PSSA should be augmented to incorporate waters that are an important habitat for this endangered population.